Types of lice (Insecta, Phthiraptera) housed in the Museo de La Plata, Argentina - Abrahamovich, Alberto H.; Lucia, Mariano; Díaz, Norma B.; Batiz, Maria F. R.; Castro, Dolores D. C. (Zootaxa, 2006)
The 333 type specimens of lices (Phthiraptera) housed at the Museo de La Plata (División Entomología), Argentina are listed, and current information on categories of types, collections and hosts provided. The types belong to 62 species and one subspecies described principally by Dolores del Carmen Castro and Armando C. Cicchino.